1994
DOI: 10.1152/jappl.1994.77.1.415
|View full text |Cite
|
Sign up to set email alerts
|

No lung toxicity after repeated aerosol or intravenous delivery of plasmid-cationic liposome complexes

Abstract: The safety aspects of human gene therapy are of paramount importance in developing an ideal system for gene transfer. Lipofection using DNA in the form of a plasmid has been shown to successfully transfect the lungs when administered either intravenously or by aerosol. We have shown that repeated intravenous or aerosol administration of a plasmid containing the recombinant human alpha 1-antitrypsin gene and a cytomegalovirus promoter complexed to cationic liposomes results in no adverse effects on pulmonary hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(40 citation statements)
references
References 0 publications
1
39
0
Order By: Relevance
“…11 The safety of the in vivo use of a variety of liposome preparations has been demonstrated in sevOur results indicate that both intra-renal-pelvic and intra-renal-arterial injections effectively deliver DNA to eral studies using experimental animals 12 and also in clinical trials. [13][14][15] The safety issue was also addressed in the renal tubules. In the former, most tubules in the outer medulla appeared to be transfected while the inner medour study as we demonstrated that BUN levels were within normal range after gene therapy and that there ullary cells were spared.…”
Section: Effects Of Liposome On Gene Transfermentioning
confidence: 99%
“…11 The safety of the in vivo use of a variety of liposome preparations has been demonstrated in sevOur results indicate that both intra-renal-pelvic and intra-renal-arterial injections effectively deliver DNA to eral studies using experimental animals 12 and also in clinical trials. [13][14][15] The safety issue was also addressed in the renal tubules. In the former, most tubules in the outer medulla appeared to be transfected while the inner medour study as we demonstrated that BUN levels were within normal range after gene therapy and that there ullary cells were spared.…”
Section: Effects Of Liposome On Gene Transfermentioning
confidence: 99%
“…Different charge/ compositions of lipids in the liposomes have been used, with cationic liposomes the most frequent (91)(92)(93)(94)(95)(96)(97). AAT serum expression levels could be increased and sustained longer with partial hepatectomy after the DNA/liposome delivery (93,96,98).…”
Section: Plasmid Vectorsmentioning
confidence: 99%
“…Canonico and colleagues (91, 92) used cationic liposomes complexed to plasmids for targeting the respiratory epithelium by aerosol delivery to rabbits. Human AAT was detected in secretory epithelial cells of the airway and along the alveolar epithelium up to 7 days after a single administration (92) and 4 weeks with repeated administration (91).…”
Section: Plasmid Vectorsmentioning
confidence: 99%
“…In fact, proto-oncogene occurs in many human cancer cells, studies from other groups have shown the low toxicity including approximately 30% of breast cancer and of DNA-liposome complex administration in mice, 15-17 ovarian cancer; and it is correlated with poor patient nonhuman primates 15,17 and humans. [18][19][20] Repeated prognosis and shorter survival. [1][2][3][4] Because down-reguadministration of DNA-liposome complex can be practilation of HER-2/neu is able to reverse the transformation cally performed to reach higher gene transfer efficiency.…”
Section: Introductionmentioning
confidence: 99%